2023
DOI: 10.3389/fonc.2022.1057532
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and clinical profiles of 160 papillary thyroid cancers with lateral neck lymph node metastasis

Abstract: BackgroundLymph node metastasis is widespread in papillary thyroid cancer (PTC). Patients are more vulnerable than those with central lymph node metastasis if they have lateral neck lymph node metastasis (LLNM). There are few researches focus on the correlation between clinical characteristics and genetic profile of PTC with LLNM. In this study, we aimed to analyze the clinical and genetic features of PTC with LLNM.MethodsA total of 160 primary tumor samples derived from PTC patients with LLNM were involved. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Within the metastatic setting however, the molecular characterization of the metastases from distinct body locations in patients with PTCs and PDTCs is rather scarce. A recent study has focused on the molecular analysis of 160 PTC patients with lateral neck lymph node metastasis (LNMs), and noticed a high frequency of BRAF mutations (68%), followed by RET translocations (17%) and TERT promoter mutations (5%) [3]. An additional genetic study of 8 PTC patients with symptomatic bone metastases revealed a high frequency of TERT promoter mutations (88%) and RAS mutations (50%) affecting these patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…Within the metastatic setting however, the molecular characterization of the metastases from distinct body locations in patients with PTCs and PDTCs is rather scarce. A recent study has focused on the molecular analysis of 160 PTC patients with lateral neck lymph node metastasis (LNMs), and noticed a high frequency of BRAF mutations (68%), followed by RET translocations (17%) and TERT promoter mutations (5%) [3]. An additional genetic study of 8 PTC patients with symptomatic bone metastases revealed a high frequency of TERT promoter mutations (88%) and RAS mutations (50%) affecting these patients [4].…”
Section: Introductionmentioning
confidence: 99%
“…The B-Raf proto-oncogene ( BRAF ) encodes a cytoplasmic serine/threonine kinase with a key role in regulating the mitogen-activated protein kinase signal transduction pathway [ 9 ]. The BRAF V600E mutation in exon 15 of the BRAF gene has been studied in different cancers, including thyroid cancers [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. Induction of the BRAF V600E mutation in thyroid cells may lead to frequent hypermethylation [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The BRAF V600E mutation is common in thyroid cancer [ 13 , 15 , 16 , 18 , 22 , 23 , 25 ], as is DNA methylation [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. However, the interaction or association between them is not well-studied.…”
Section: Introductionmentioning
confidence: 99%